Relativism, alternate history, and the forgetful reader : reading science fiction and historiography - Thiess, Derek, 1981- (Lexington Books, 2014)
This book channels the speculative power of science fiction to examine the limits of postmodern philosophies of history. By contrasting the questioning nature of science fiction to postmodern philosophy of history, it finds that this postmodernism often engages in a forgetful, even ahistorical, reading of the past.